2020
DOI: 10.1039/c9cp05006j
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium structures of water molecules confined within a multiply connected carbon nanotube: a molecular dynamics study

Abstract: Water confinement inside a carbon nanotube (CNT) has been one of the most exciting subjects of both experimental and theoretical interest. Most of the previous studies, however, considered CNT structures with simple cylindrical shapes. In this paper, we report a classical molecular dynamics study of the equilibrium structural arrangement of water molecules confined in a multiply connected carbon nanotube (MCCNT) containing two Y-junctions. We investigate the structural arrangement of the water molecules in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…We obtain 1.7 in the feed zone, and 1.4 and 1.2 inside the pristine and wall-functionalized membranes, respectively, in agreement with a recent study of water confined in (7, 7) and (14,14) carbon nanotubes that reported 0.9 and 1.2 hydrogen bonds per water molecule, respectively. [57] Typically, the water flux is inversely proportional to the thickness of the membrane. According to Table 3, we find for the pristine CHC membrane that the water permeability is reduced by 12% when the thickness is doubled from 1.2 to 2.4 nm and by 38% when the thickness is increased by a factor of 5 from 1.2 to 6.0 nm.…”
Section: Results Andmentioning
confidence: 99%
See 1 more Smart Citation
“…We obtain 1.7 in the feed zone, and 1.4 and 1.2 inside the pristine and wall-functionalized membranes, respectively, in agreement with a recent study of water confined in (7, 7) and (14,14) carbon nanotubes that reported 0.9 and 1.2 hydrogen bonds per water molecule, respectively. [57] Typically, the water flux is inversely proportional to the thickness of the membrane. According to Table 3, we find for the pristine CHC membrane that the water permeability is reduced by 12% when the thickness is doubled from 1.2 to 2.4 nm and by 38% when the thickness is increased by a factor of 5 from 1.2 to 6.0 nm.…”
Section: Results Andmentioning
confidence: 99%
“…We obtain 1.7 in the feed zone, and 1.4 and 1.2 inside the pristine and wall‐functionalized membranes, respectively, in agreement with a recent study of water confined in (7, 7) and (14, 14) carbon nanotubes that reported 0.9 and 1.2 hydrogen bonds per water molecule, respectively. [ 57 ]…”
Section: Resultsmentioning
confidence: 99%